A Letter to Ben Bernanke - Mankiw, N. Gregory (American Economic Review, 2006)
This paper discusses five questions the incoming chairman of the Federal Reserve must ponder as he assumes his new post. How important are monetary rules? Should the Fed adopt inflation targeting? Should he be free with his opinions? Should he be a high-profile public figure? Is it more important to be good or lucky?